Extreme fieldwork: flame-sealed capillaries versus frozen serums to estimate body composition of southern elephant seals (Mirounga leonina) using isotopic dilution - Laura M. Charlanne; Alexandre Zahariev; Christophe Guinet; Erwan Piot; Jérôme Badaut; Caroline Gilbert; André Ancel; Audrey Bergouignan (Polar Biology, 2024)

Adding a diversity of legumes to a crop decision-support system: Maintaining satisfactory accuracy while keeping the model simple - M. Bedu; L. Lefèvre; A. Dupont; P. Dubrulle; R. Reau; P. Debaeke; M. Guinet; M.-H. Jeuffroy; P. Maury; A. Schneider; C. Schoving; P. Thiébeau; et al. (European Journal of Agronomy, 2023)

Long Distance Runners in the Marine Realm: New Insights Into Genetic Diversity, Kin Relationships and Social Fidelity of Indian Ocean Male Sperm Whales - Justine Girardet; Francois Sarano; Gaëtan Richard; Paul Tixier; Christophe Guinet; Alana Alexander; Véronique Sarano; Hugues Vitry; Axel Preud’homme; René Heuzey; Ana M. Garcia-Cegarra; Olivier Adam; et al. (Frontiers in Marine Science, 2022)
Adult male sperm whales ( Physeter macrocephalus ) are long distance runners of the marine realm, feeding in high latitudes and mating in tropical and subtropical waters where stable social groups of females and immatures live. Several areas of uncertainty still limit our understanding of their social and breeding behavior, in particular concerning the potential existence of geographical and/or social fidelities. In this study, using underwater observation and sloughed-skin sampling, we looked for male social fidelity to a specific matrilineal sperm whale group near Mauritius. In addition, we captured a wider picture of kin relationships and genetic diversity of male sperm whales in the Indian Ocean thanks to biopsies of eight individuals taken in a feeding ground near the Kerguelen and Crozet Archipelagos (Southern Indian Ocean). Twenty-six adult male sperm whales were identified when socializing with adult females and immatures off Mauritius. Sloughed-skin samples were taken from thirteen of them for genetic analysis. Long-term underwater observation recorded several noteworthy social interactions between adult males and adult females and/or immatures. We identified seven possible male recaptures over different years (three by direct observation, and four at the gametic level), which supports a certain level of male social fidelity. Two probable first- and thirty second-degree kin relationships were highlighted between members of the social unit and adult males, confirming that some of the adult males observed in Mauritian waters are reproductive. Male social philopatry to their natal group can be excluded, as none of the males sampled shared the haplotype characteristic of the matrilineal social group. Mitochondrial DNA control region haplotype and nucleotide diversities calculated over the 21 total male sperm whales sampled were similar to values found by others in the Indian Ocean. Our study strongly supports the existence of some levels of male sperm whale social fidelity, not directed to their social group of birth, in the Indian Ocean. Males sampled in breeding and feeding grounds are linked by kin relationships. Our results support a model of male mediated gene flow occurring at the level of the whole Indian Ocean, likely interconnected with large-scale geographical fidelity to ocean basin, and a small-scale social fidelity to matrilineal social groups.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Laccaria bicolor MiSSP8 is a small‐secreted protein decisive for the establishment of the ectomycorrhizal symbiosis - Clément Pellegrin; Yohann Daguerre; Joske Ruytinx; Frédéric Guinet; Minna Kemppainen; Nicolas Frei dit Frey; Virginie Puech‐Pagès; Arnaud Hecker; Alejandro G. Pardo; Francis M. Martin; Claire Veneault‐Fourrey (Environmental Microbiology, 2019)
Summary The ectomycorrhizal symbiosis is a predominant tree–microbe interaction in forest ecosystems sustaining tree growth and health. Its establishment and functioning implies a long‐term and intimate relationship between the soil‐borne fungi and the roots of trees. Mycorrhiza‐induced Small‐Secreted Proteins (MiSSPs) are hypothesized as keystone symbiotic proteins, required to set up the symbiosis by modifying the host metabolism and/or building the symbiotic interfaces. L . bicolor MiSSP8 is the third most highly induced MiSSPs in symbiotic tissues and it is also expressed in fruiting bodies. The MiSSP8‐ RNAi knockdown mutants are strongly impaired in their mycorrhization ability with Populus , with the lack of fungal mantle and Hartig net development due to the lack of hyphal aggregation. MiSSP8 C‐terminus displays a repetitive motif containing a kexin cleavage site, recognized by KEX2 in vitro . This suggests MiSSP8 protein might be cleaved into small peptides. Moreover, the MiSSP8 repetitive motif is found in other proteins predicted secreted by both saprotrophic and ectomycorrhizal fungi. Thus, our data indicate that MiSSP8 is a small‐secreted protein involved at early stages of ectomycorrhizal symbiosis, likely by regulating hyphal aggregation and pseudoparenchyma formation.

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

An alternative method for correcting fluorescence quenching - L. Biermann; C. Guinet; M. Bester; A. Brierley; L. Boehme (Ocean Science, 2015)
Under high light intensity, phytoplankton protect their photosystems from bleaching through non-photochemical quenching processes. The consequence of this is suppression of fluorescence emission, which must be corrected when measuring in situ yield with fluorometers. We present data from the Southern Ocean, collected over five austral summers by 19 southern elephant seals tagged with fluorometers. Conventionally, fluorescence data collected during the day (quenched) were corrected using the limit of the mixed layer, assuming that phytoplankton are uniformly mixed from the surface to this depth. However, distinct deep fluorescence maxima were measured in approximately 30% of the night (unquenched) data. To account for the evidence that chlorophyll is not uniformly mixed in the upper layer, we propose correcting from the limit of the euphotic zone, defined as the depth at which photosynthetically available radiation is ~ 1% of the surface value. Mixed layer depth exceeded euphotic depth over 80% of the time. Under these conditions, quenching was corrected from the depth of the remotely derived euphotic zone Zeu, and compared with fluorescence corrected from the depth of the density-derived mixed layer. Deep fluorescence maxima were evident in only 10% of the day data when correcting from mixed layer depth. This was doubled to 21% when correcting from Zeu, more closely matching the unquenched (night) data. Furthermore, correcting from Zeu served to conserve non-uniform chlorophyll features found between the 1% light level and mixed layer depth.

Ontogeny of aquatic behaviours in Antarctic fur seal (Arctocephalus gazella) pups in relation to growth performances at Kerguelen Islands - C. Gastebois; M. Viviant; C. Guinet (Polar Biology, 2011)

WISE-2005: effect of aerobic and resistive exercises on orthostatic tolerance during 60 days bed rest in women - Patrick Guinet; Suzanne M. Schneider; Brandon R. Macias; Donald E. Watenpaugh; Richard L. Hughson; Anne Pavy Le Traon; Jean-Yves Bansard; Alan R. Hargens (European Journal of Applied Physiology, 2009)

Multiple origins of vagrant Subantarctic fur seals: a long journey to the Brazilian coast detected by molecular markers - Juliana Machado Ferreira; Larissa Rosa de Oliveira; Louise Wynen; Marthán N. Bester; Christophe Guinet; Nadia Moraes-Barros; Felipe Mello Martins; Mônica M. C. Muelbert; Ignacio B. Moreno; Salvatore Siciliano; Paulo Henrique Ott; João Stenghel Morgante (Polar Biology, 2008)

Evaluation of Six Commercial Systems for Identification of Medically Important Yeasts - L. Buchaille; A. M. Freydière; R. Guinet; Y. Gille (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Evaluation of six commercial systems for identification of medically important yeasts - L. Buchaille; A. M. Freydière; R. Guinet; Y. Gille (European Journal of Clinical Microbiology & Infectious Diseases, 1998)